Association of low Serum Magnesium level with occurrence of Ventricular Arrhythmia in patients with Acute Myocardial Infarction (Bangladesh Heart Journal, 2020)
Background: Acute Myocardial Infarction is the leading cause of morbidity and mortality throughout the world. Its prevalence among developing countries has increased significantly over the past two decades. Acute myocardial infarction is associated with electrolyte imbalance most commonly hypomagnesemia and hypokalaemia. Both are associated with ventricular arrhythmia which can lead to increase hospital mortality and morbidity.Objectives: To find out association of hypomagnesemia with ventricular arrhythmia in patients with acute myocardial infarction. Methods: Patients with acute myocardial infarction admitted in the department of Cardiology, DMCH, within the study period and who fulfilled the inclusion and exclusion criteria were taken as study sample. Informed consent was taken from all patients and then the patients were evaluated by detailed history, clinical examination and relevant investigations. Serum magnesium level was measured after admission. The sample population was Grouped into Group A(Acute myocardial infarction with normal serum magnesium) and Group B(Acute myocardial infarction with hypomagnesemia). Patients were followed up regularly till discharge or death for evidence of ventricular arrhythmia. Then the obtained data was analysed with SPSS 22.0.Results: Among 110 patients of Acute MI, 44 patients were in Group A who had plasma magnesium level e”0.7 mmol/ l and 66 patients were in Group B who had plasma magnesium level